Integrative Analysis of Metabolome and Transcriptome Profiles to Evaluate the Response Mechanisms of Carex adrienii to Shade Conditions - Tao Guo; Shumin Wang; Zhong Tian; Shuang Chen; Xuemei Li; Shihui Zou; Zhijian Tan; Jiao Wang; Sheng Wang; Lijiao Ai; Shunzhao Sui (Agronomy)
Carex is a type of herbaceous plant with high application value, playing an important role in the urban periphery. Due to its unique morphology and ecological characteristics, Carex is widely used in various fields, such as landscaping, ecological restoration and soil and water conservation, which help to maintain the balance of the ecosystem. In order to explore the potential molecular mechanisms of shade tolerance in Carex, transcriptome and metabolome sequencing were performed on the leaves of the shade = tolerant species Carex adrienii E. G. Camus. under 80% shade and no shade conditions. Compared to control group (CK), the total chlorophyll, chlorophyll a, chlorophyll b and total carotenoid content in the C. adrienii leaves of the shading treatment were significantly upregulated. The antioxidant enzyme activity of the leaves, including superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), were also remarkably upregulated in the shading treatment groups. In addition, the net photosynthesis rate (Pn), stomatal conductance (Gs) and transpiration rate (Tr) of the leaves were reduced, and the intercellular CO2 concentration (Ci) of the leaves was increased under shade. The transcriptome identified 5056 differentially expressed genes (DEGs) and the metabolome identified 889 differential accumulated metabolites (DAMs) in three treated samples. The integrated transcriptomic and metabolomic analyses results showed that the DEGs and DAMs were enriched in photosynthesis, plant hormone signal transduction and flavonoid biosynthesis synthesis pathways. The ABA content of the C. adrienii leaves was significantly increased under shade. Therefore, the shading conditions led to changes in chlorophyll and abscisic acid (ABA), as well as the accumulation of flavonoids in C. adrienii, both of which were achieved by regulating genes involved in photosynthesis, plant hormone signal transduction and flavonoid biosynthesis molecular networks. Our results provide new knowledge for the molecular response and metabolic regulatory mechanisms of C. adrienii to shade stress, and valuable genetic resources for C. adrienii shade tolerance molecular breeding.